2019
DOI: 10.3389/fphys.2019.00365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mitochondrial Respiration in M. triceps brachii and M. vastus lateralis Between Elite Cross-Country Skiers and Physically Active Controls

Abstract: Rationale The main purposes of this study were to compare mitochondrial respiration in M. triceps brachii and M. vastus lateralis between elite cross-country (XC) skiers and physically active controls (CON), and to explore the associations between mitochondrial respiration in these muscles and peak oxygen uptake ( O 2peak ) in arm- and leg-dominant exercise modes. Methods Thirteen male elite XC skiers (age: 25 ± 4; peak oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The 7 studies collected samples from the muscle groups gastrocnemius, soleus, latissimus dorsi, triceps brachii, lumbar multifidus, erector spinae, and upper trapezius. 11,32,[35][36][37][38][39] The terms used in the majority to describe the location of the vastus lateralis were "mid-belly," "middle portion," "mid-point," and "lateral aspect." Other authors described the selected location on the vastus lateralis as "1/3 or 2/3 the distance from the patella to anterior superior iliac spine (ASIS)" or "50% the distance from the greater trochanter to the lateral femoral epicondyle."…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 7 studies collected samples from the muscle groups gastrocnemius, soleus, latissimus dorsi, triceps brachii, lumbar multifidus, erector spinae, and upper trapezius. 11,32,[35][36][37][38][39] The terms used in the majority to describe the location of the vastus lateralis were "mid-belly," "middle portion," "mid-point," and "lateral aspect." Other authors described the selected location on the vastus lateralis as "1/3 or 2/3 the distance from the patella to anterior superior iliac spine (ASIS)" or "50% the distance from the greater trochanter to the lateral femoral epicondyle."…”
Section: Resultsmentioning
confidence: 99%
“…35,36,45,46,48,50,70 One study reported measuring skinfold thickness to estimate the depth of the biopsy needle 69 ; however, they did not report their protocol. Prior to the introduction of the microbiopsy needle, numerous authors reported that an incision was made in the skin and fascia with a hypodermic needle (14, 18, and 23 G) 23,50,71,72 or a co-axial/ cannula introducer 35,37,55,[73][74][75][76][77][78][79] to create or maintain a "pilot hole" for multiple passes if the study design required larger sample size (mg) per time point for analysis. Other authors did not report how skin and fascia were incised to admit a microbiopsy needle into the muscle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, upper-body muscles are reported to extract ~10% lower O 2 than leg muscles (Calbet et al, 2005 ) and contribute, together with a lower vascular conductance (Calbet et al, 2004 ), to lower VO 2peak values in DP compared to running (Losnegard et al, 2019 ). Recently, Berg et al ( 2019 ) found higher mitochondrial respiration in the upper body but equal in the lower body when comparing XC skiers and physically active controls. It may be hypothesized that the average DP-VO 2peak /RUN-VO 2max ratio among LDS in this study, which to our knowledge is the highest ever reported in the literature (Losnegard, 2019 ), is due to the high volumes of DP-specific training in LDS which may further increase O 2 extraction and/or enhance mitochondrial respiration in upper-body muscles beyond what has previously been shown.…”
Section: Discussionmentioning
confidence: 97%